Pear pomace water extract reduces adiposity in vivo and in vitro by activating the AMPK-dependent pathway - Mi-Kyoung You; Gwang-Woong Go; Hwa-Jin Kim; Jin Rhyu; Hyeon A Kim (Asian Pacific Journal of Tropical Biomedicine, 2020)
Objective: To explore the inhibitory effect of water extract from pear pomace on abdominal fat accumulation and its underlying mechanism in high fat diet-fed animals. Methods: Three groups of male C57BL/6J mice were fed with a 60% kcal fat diet for 8 weeks. Pear pomace water extract (200 or 400 mg/kg body weight) was administered once daily via oral gavage. To confirm the possibility of the water extract of pear pomace acting as an activator of adenosine 5’-monophosphate- activated protein kinase (AMPK), differentiation of 3T3-L1 preadipocytes was induced in the presence of the water extract of pear pomace with or without compound C. Body weight, food efficacy ratio, insulin resistance, and adipogenic protein expression were measured. Moreover, in the 3T3-L1 cells, lipid content and lipogenesis-related proteins were measured using Oil Red O staining and Western blotting analysis. Results: Body weight gain and total abdominal fat weight were reduced in mice treated with pear pomace water extract. Pear pomace water extract reduced fasting blood glucose and insulin, thereby reducing the homeostatic model assessment of insulin resistance. It also resulted in dose-dependent decreases in triglyceride, total cholesterol, and low-density lipoprotein- cholesterol. The protein expression of p-AMPK increased, while the expression of AMPK-downstream proteins including PPAR-γ, C/ EBPa, SREBP-1c, ACC, and FAS decreased in the adipose tissue of mice treated with pear pomace water extract. Furthermore, the inhibition of AMPK by compound C blocked pear pomace water extract-induced reduction of lipid content and the expression of lipogenesis-related genes. Conclusions: Pear pomace water extract prevents fat accumulation both in vivo and in vitro by activating AMPK.